MANAJEMEN PENGAWASAN KEPEGAWAIAN DAERAH KABUPATEN SUKABUMI MENURUT UNDANG-UNDANG NOMOR 32 TAHUN 2004 TENTANG PEMERINTAHAN DAERAH JUNCTO UNDANG-UNDANG NOMOR 5 TAHUN 2014 TENTANG APARATUR SIPIL NEGARA (ASN) JUNC TO UNDANG-UNDANG NOMOR 43 TAH - MUNANDAR WAHYUDIN SUGANDA (LP2M CBI PRESS, 2016)
The objectives to be achieved by the state welfare law is how the state gives a sense of justice, asense of security in an orderly and wellbeing for all society. Destination can be achieved moving the wheels of government in the broad sense of law (Rechstate). Directing society ekonomic sector, and mobilize community participation in development. Management and supervision of Civil Servants (PNS) is an integral and ineparable. Management in a universal sense of planing organizing, directing, motivating, and oversight of implementation of the mechanism of action and work to achieve the goal. In this study, the identification of the issues discussed are: Fist, the background of the need for oversight of the Civil Service District Sukabumi. Second, government environments appropriate supervision Application of Law No. 32 of 2004 on regional Government Junc To Law Number 5 of 2014 On the State Civil Apparatus Junc To Act Number 43 of 1999 On The Fundamentals of civil Government’s environment Sukabumi. Third, issues and efforts in monitoring the implementation of the civil Service within the Local Government Act Sukabumi accordance Law Number 5 of 2014 On the State Civil Apparatus Junk To Law Number 43 of 1999 On Fundamentals of Civil Service. Enforcement of disipline as the government Regulation Number 53 of 2010 on the Disipline of Civil Servant is seen as a necessity to improve and maintain the performance of the civil Service in carrying out duties for the benefit of society. Merit system to aim for in Act Number 5 of 2014 On State Civil Apparatus (ASN) is the basis that civil servants have the qualifications, competence, and performaance in a fair and reasonable with regardless of politics, race, color, gender, status, age ordisability conditions so as to create a public service that plenary for the welfare and public order. This study was conducted using normative juridical sociological approach, trough a study of the legislation, through literature, papers, journals, and the media that has to do with this research. Key Word : Management of personel, Personel of region, Personel Goverment region.